Quality Improvement and Management System Development of School Guidance and Counseling Services - Sunaryo Kartadinata (Universitas Negeri Malang, 2016)
The study aimed at developing an appropriate model to improve quality and develop management system of school guidance and counseling services. The study was divided into three phases conducted for three years in different school levels ranging from primary to higher education, in Java and Sumatra. The extension of the study was also conducted in Kindergarten and Special Education setting. The whole study came up with: the general models which provided a basis for developing frame work of guidance and counseling in every school level; frame work of guidance and counseling for every school level; standardized inventory of students' developmental tasks developed in a computerized system; and learning packages developed based on students' needs and development. Research findings show that the models were feasible and applicable and gave an improvement of quality of school guidance and counseling services and management